2019
DOI: 10.21203/rs.2.18832/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Chlorhexidine use for cord care at Kangundo level 4 Hospital

Abstract: Background: Sepsis continues to be an important cause of morbidity and mortality in neonates. One of the most important portals of entry for infections is the umbilical cord. Proper care of the cord can prevent many of these cases of sepsis and hence reduce neonatal mortality rates. In Kenya, the use of chlorhexidine digluconate (CHX) gel was introduced to scale in 2016 and received with mixed reactions in some hospitals with reports of medication errors and ineffectiveness being received. This study sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, it is not clear whether its continued use despite chlorhexidine scale up could be attributed to lack of awareness or unacceptability of the later among healthcare workers. A focused group discussion in Uganda, conducted 3 years after chlorhexidine gel was scaled-up, showed that most healthcare workers considered methylated spirit better and moreeffective than chlorhexidine gel and this may affect the information given to clients [26]. Reports from post scale-up Nigerian quasi experimental and small randomized trials indicate that the efficacy of methylated spirit was comparable to chlorhexidine gel and that the later was associated with delayed cord separation which was a source of dissatisfaction for the users [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether its continued use despite chlorhexidine scale up could be attributed to lack of awareness or unacceptability of the later among healthcare workers. A focused group discussion in Uganda, conducted 3 years after chlorhexidine gel was scaled-up, showed that most healthcare workers considered methylated spirit better and moreeffective than chlorhexidine gel and this may affect the information given to clients [26]. Reports from post scale-up Nigerian quasi experimental and small randomized trials indicate that the efficacy of methylated spirit was comparable to chlorhexidine gel and that the later was associated with delayed cord separation which was a source of dissatisfaction for the users [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a descriptive cross-sectional study on the assessment of chlorohexidine use in Kangundo Level 4 hospital in Kenya showed mixed cord care practices among respondents. Feedback from the focused group discussions indicated that respondents felt the methylated spirit was more effective than CHX, lack of use of the CHX Gel in maternity immediately after birth as recommended and no clear instructions on how to apply the gel coupled with the erratic supply of gel leading healthcare facilities to opt for spirit (Ambale et al, 2019) contributed to minimal uptake. Similarly, a case-control study to assess umbilical care hygiene and neonatal sepsis relationship in a primary healthcare facility in an urban setting found that Chlorhexidine/surgical spirit were used for cord care among 79.2% of caregivers in the control group compared to 35.6% of the cases (Moraa et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the use of CHX was introduced in healthcare facilities in Kenya (Ambale et al, 2019;Health et al, 2016), and research conducted in Bungoma county shows high acceptability of CHX use among caregivers and healthcare workers (Muriuki et al, 2017). The introduction of CHX was, however met with mixed reactions (Ambale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation